Effects of various manufacturing parameters and test temperature and crosshead displacement rate on the peel resistance of UHMWPE composites - Omar Banabila; Noora Alahmed; Rubayea Alameri; Rafael Santiago; Kamran A. Khan; Wesley J. Cantwell (Results in Engineering)
This study examines the peel resistance and fracture energy of an ultra-high molecular weight polyethylene (UHMWPE) composite, HB26. Peel tests were initially conducted on different sample widths to establish the critical fracture energy of the material, which was found to plateau at approximately 2000 J/m². Thin UHMWPE laminates were then manufactured under varying processing conditions, with pressures ranging from 20 to 35 MPa and temperatures between 120 and 135°C, to evaluate their influence on peel resistance. The results showed that fracture energy remained relatively stable across this processing window, confirming a broad manufacturing tolerance. The effect of displacement rate and test temperature on delamination resistance was also investigated by conducting peel tests at different displacement rates from 0.2 to 200 mm/min and temperatures ranging from 25 to 100°C. Fracture energy was observed to increase significantly with higher displacement rates, reflecting the rate-sensitivity of the matrix. Conversely, increasing the temperature led to a marked reduction in peel resistance due to softening of the matrix. Scanning electron microscopy (SEM) analysis revealed the primary failure mechanisms, including fiber pull-out, localized matrix ductility, and fiber fracture across all tested samples. This study attempts to optimize the processing cycle and performance of UHMWPE composites in applications requiring reliable delamination resistance.